Infrared Thermal Imaging for Evaluation of Clubfoot After the Ponseti Casting Method—An Exploratory Study - Ganesan, Balasankar; Yip, Joanne; Luximon, Ameersing; Gibbons, Paul J.; Chivers, Alison; Balasankar, Suchita Kothe; Tong, Raymond Kai-Yu; Chai, Rifai; Al-Jumaily, Adel (Frontiers in Pediatrics, 2021)
Background: Conservative treatment, Ponseti method, has been considered as a standard method to correct the clubfoot deformity among Orthopedic society. Although the result of conservative methods have been reported with higher success rates than surgical methods, many more problems have been reported due to improper casting, casting pressure or bracing discomfort. Nowadays, infrared thermography (IRT) is widely used as a diagnostic tool to assess musculoskeletal disorders or injuries by detecting temperature abnormalities. Similarly, temperature evaluation can be added along with subjective evaluation to predict if there is any casting pressure or overcorrections of the foot- related complications. Purpose: The main purpose of this study is to explore the foot skin temperature changes before and after using of manipulation and weekly castings. Methods: This is an explorative study design. IRT- E33 FLIR thermal imaging camera was used to collect thermal images before and after casting intervention. A total of 120 thermal images (Medial region of the foot - 24, Lateral side of the foot - 24, Dorsal side of the foot -24 , Plantar side of the foot -24 , and Heel area - 24) were collected from the selected regions of the clubfoot. Results: Univariate statistical analysis showed that significant temperature changes only in some regions of the foot after casting, especially, at the second (M=32.05°C, SD=0.77, p=0.05), third (M=31.61, SD=1.11; 95% CI: 31.27-31.96; p=0.00), and sixth week of evaluation on the lateral side of the foot (M=31.15°C, SD=1.59; 95% CI: 30.75-31.54, p=.000). There was no significant temperature changes throughout the weekly casting in the medial side of the foot. A significant temperature changes were noticed in the heal areas of foot after the third and fourth weeks of casting. Conclusion: Overall, we found that the foot skin temperature decreased in the dorsal and lateral side of the foot in the sixth week of thermography evaluation. The finding of this study shows that the infrared thermography (IRT) might be useful as an adjunct assessment tool to evaluate the thermophysiological changes, which can be used to predict the complications caused by improper casting, manipulative or stretching and casting-pressure related complications